Nonergodic diffusion of single atoms in a periodic potential - Kindermann, Farina; Dechant, Andreas; Hohmann, Michael; Lausch, Tobias; Mayer, Daniel; Schmidt, Felix; Lutz, Eric; Widera, Artur (Nature Physics, 2017)
Diffusion can be used to infer the microscopic features of a system from the observation of its macroscopic dynamics. Brownian motion accurately describes many diffusive systems, but non-Brownian and nonergodic features are often observed on short timescales. Here, we trap a single ultracold caesium atom in a periodic potential and measure its diffusion. We engineer the particle-environment interaction to fully control motion over a broad range of diffusion constants and timescales. We use a powerful stroboscopic imaging method to detect single-particle trajectories and analyse both non-equilibrium diffusion properties and the approach to ergodicity. Whereas the variance and two-time correlation function exhibit apparent Brownian motion at all times, higher-order correlations reveal strong non-Brownian behaviour. We additionally observe the slow convergence of the exponential displacement distribution to a Gaussian and-unexpectedly-a much slower approach to ergodicity, in perfect agreement with an analytical continuous-time random-walk model. Our experimental system offers an ideal testbed for the detailed investigation of complex diffusion processes.
CRIS-Team Scopus Importer:2023-03-27